Modelling sound radiation from a baffled vibrating plate for different boundary conditions using an elementary source technique - Putra, Azma; Ab. Latif, Nurain Shyafina; Thompson, David J.; Muhammad, Noryani; Mohd Nor, Mohd Jailani; Nuawi, Zaki (Inter-Noise 2014, 2014)
Analytical models of the sound radiation a rectangular plate are often based on simply supported edges for mathematical convenience. Models for other boundary conditions also exist, but mostly these employ rather complicated analytical calculations. This paper presents an analytical model of the radiation efficiency for a baffled plate using a discrete elementary source model. The model requires only the a knowledge of the spatial distribution vibration velocity of the panel and hence this surface velocity can be calculated conveniently by using the established mobility equations for different plate boundary conditions. This is then included in the discretized Rayleigh integral to calculate the radiated sound pressure to the far-field. Variability of the radiation efficiency for different forcing locations and its average value are presented here for several combinations of boundary conditions. Experimental results are presented for free and clamped edges which show reasonable agreement with the predicted results.